ISLAMIC TEACHERS’ PERCEPTIONS OF USING GAMIFICATION IN SAUDI ARABIAN ELEMENTARY SCHOOLS - Alwadai, Mesfer (Advances in Social Sciences Research Journal, 2019)
The current study aimed to examine the practice-based perceptions of Islamic teachers of Saudi Elementary school who do teach with gamification - either playing or creating games-in classrooms in order assess their opinions of using games in their teaching Islamic lessons courses. Semi-structured interviews were conducted with 192 Saudi elementary education Islamic teachers. The study found that the use of gamification in the Saudi elementary schools played a pivotal role in enhancing the elementary students’ intrinsic and extrinsic motivations, with a total mean hit 4.67. Also, gamification creating attractive learning environment received the second highest rating, with total average of 4.48. In addition, the positive effects of gamification for enhancing student’s collaboration work with others was the third highest rating, with total mean of 4.37. The findings revealed that most Islamic teachers of Saudi elementary schools who actually use gamification in their classrooms perceived elementary school student engagement with a game and cognitive learning outcome as effects of the use of games in formal teaching settings. Also, the findings of the study recommend there is a need for further studies to examine perceptions of teachers of other disciplines, such as languages, arts, social science, science, computer science and the like of using gamification in teaching and learning. Also, qualitative studies may be conducted by the researchers in these domains , interviews with students, and classroom observation can be carried out to investigate Saudi students’ perceptions in different educational levels of using gamification in education The pedagogical implications of these findings for the use of gamification in teachers’ educational practice are discussed.